Microwave-assisted synthesis of novel 5-trichloromethyl-4,5-dihydro-1H-1-pyrazole methyl esters under solvent free conditions - Beck, Paulo (2014)
Submitted by Taís Renata Pereira Amorim (tatahamorim_sjn@hotmail.com) on 2014-06-10T20:06:47Z No. of bitstreams: 1 Microwave-Assisted Synthesis of Novel 5-Trichloromethyl-4,5-dihydro-1H-1-pyrazole.pdf: 130352 bytes, checksum: cec328afdac8691dcf411cd7be36d13d (MD5)